Detritus processing in lentic cave habitats in the neotropics - Marconi Silva; Rafaelly Rezende; Rodrigo Lopes Ferreira (Subterranean Biology, 2013)
Lentic cave habitats are almost always heterotrophic habitats where there are food and oxygen input from the surface. This hydrological exchange seems to be the key factor shaping most groundwater communities. Litter processing in cave water environments has not been experimentally studied as much as it has in lotic subterranean systems, although detritus is likely a critical resource for organisms inhabiting shallow groundwater habitats. The present study sought to evaluate the processing rates and the nitrogen and phosphorous dynamics in plant debris deposited in lentic habitats of two Neotropical limestone caves during 99 days. 84–10×10 cm2 litterbags with mesh sizes of 0.04 mm2 and 9 mm2 were used. In each weighed litter bag, 50 green, intact plant leaf disks (± 2.0 gr/bag) were conditioned. At the end of the experiment, the average weight loss was only 17.4%. No macroinvertebrates were found associated to the debris, but significant differences in the processing rate in relation to the cave and mesh size were observed. The weight loss rate of the plant debris was considered slow (average 0.003 K-day). The amount of nitrogen and remaining phosphorous in the plant debris in the two caves showed variations over time with a tendency to increase probably due to the development of microorganisms which assimilate nitrogen and phosphorus. The slow processing rate of the plant debris can be due mainly to the fact that these lentic cave habitats are restrictive to colonization by shredder invertebrates. Furthermore, the abrasive force of the water, which plays an important role in the processing and availability of fragmented debris for colonization by microorganisms, is absent.